Factors Affecting The Predominance Of Verstek Judgments In Divorce Cases Before The Religious Court - Nur, Muliadi; Jamil, Abdul (Prophetic Law Review, 2021)
This study examines the factors affecting the predominance of verstek judgments in the disposition of divorce cases in religious courts. It was mainly aimed at analyzing the factors that influence the settlement of divorce cases in the absence of the defendant so that the judge decides through a verstek judgment. This research used a normative legal research with a statutory approach and a legal system. The study found three primary factors in the legal system that have lead to the verstek judgments for divorce cases in religious courts. First, the existing substantial components and legal arrangements have not explicitly regulated the criteria, limitations, or reasons for the absence of defendants who who are entitled to verstek examination in divorce cases. Second, the legal structure includes the paradigm of passive judges and strong adherence to procedures, as well as the summoning of the parties by bailiffs. Third, a cultural component, including the factor of awareness of the nature of marriage and the meaning of a divorce, and the rule of law in society regarding the rules and mechanisms for divorce settlement.Keywords: Dominant factors; verstek verdict; divorce casesFaktor-Faktor Yang Mempengaruhi Predominasi Putusan Verstek Dalam Kasus Perceraian Di Hadapan Pengadilan AgamaAbstrakPenelitian ini mengkaji faktor-faktor yang mempengaruhi dominannya putusan verstek dalam disposisi perkara perceraian di pengadilan agama. Hal ini terutama bertujuan untuk menganalisis faktor-faktor yang mempengaruhi penyelesaian perkara perceraian tanpa kehadiran tergugat sehingga hakim memutuskan melalui putusan verstek. Penelitian ini menggunakan penelitian hukum normatif dengan pendekatan perundang-undangan dan sistem hukum. Studi ini menemukan tiga faktor utama dalam sistem hukum yang mengarah pada putusan verstek untuk kasus perceraian di pengadilan agama. Pertama, komponen substansial dan pengaturan hukum yang ada belum secara tegas mengatur kriteria, batasan, atau alasan tidak adanya terdakwa yang berhak pemeriksaan verstek dalam perkara perceraian. Kedua, struktur hukum meliputi paradigma hakim pasif dan kepatuhan yang kuat terhadap prosedur, serta pemanggilan para pihak oleh juru sita. Ketiga, komponen budaya, meliputi faktor kesadaran akan hakikat perkawinan dan makna perceraian, serta aturan hukum dalam masyarakat tentang aturan dan mekanisme penyelesaian perceraian.Kata kunci: Faktor dominan; putusan verstek; kasus perceraian